Anticoagulant management in patients with atrial fibrillation. - Fitzmaurice, D; Hobbs, F (2009)
Atrial fibrillation (AF) is the most common cardiac arrhythmia and is associated with a high risk of embolic stroke (cause in 15% of all strokes and 30% of strokes in those >75 years of age). Anticoagulation with warfarin will reduce stroke risk by about two thirds. The main risks of anticoagulation, namely bleeding, can be minimized by maintaining anticoagulation control within the international normalized range range of 2.0 to 3.0 (target: 2.5). To have a public health impact, patients with AF need efficient and correct identification, with appropriate treatment directed at those patients at most risk from the condition.